Mapping and Assessing Surface Morphology of Holocene Lava Flow in Krafla, NE Iceland, Using Remote Sensing - Aufaristama, Muhammad, 1991- (2015)
Iceland is well known for its volcanic activity due to being situated on the spreading Mid Atlantic Ridge and a hot spot. This landmass is located in the North Atlantic Ocean between Greenland and Norway. In the past 1000 years there were about 200 eruptions occurring in Iceland, meaning volcanic eruptions occur on average every four to five years. Iceland currently has 30 active volcano systems, distributed evenly throughout the so-called Neovolcanic Zone. One of these volcanic systems is the Krafla central volcano. Krafla is located in northern Iceland at latitude 65°42'53'' N, and longitude 16°43'40'' W. Krafla has produced two volcanic events in historic times: 1724-1729 (Myvatn Fires) and 1975-1984 (Krafla Fires). The Krafla Fires began in December 1975 and lasted until September 1984. This resulted in about 36 km2 covered by lava; a volume of 0.25-0.3 km³. Previous studies of lava surface morphology at Krafla focused on an open channel area mapped as 55% aa lava, 32% as pahoehoe, and the remaining 13% as the main lava channel. The earlier study was mostly field mapping, video recording and measuring pre-flow topography from aerial photographs. Therefore, studies by remote sensing are essential as a complementary tool to previous investigations and to extend the area of mapping. Using maximum likelihood and Spectral Angle Mapper (SAM) classification approach by selecting spectral reflectance endmembers, this study has successfully produced three detailed maps of lava surface morphology in Krafla lava field from three satellite images: SPOT 5 (Multispectral & Panchromatic), Landsat 8 OLI (Multispectral) and EO-1 Hyperion (Hyperspectral) satellite images. The overall accuracy of these lava morphology maps are 67.33% (SPOT 5), 52.67% (Landsat 8 OLI) and 61.33% (EO-1 Hyperion). These results show that remote sensing is an acceptable alternative to field mapping and assessing the lava surface morphology in the Krafla lava field. In order to get validation of the satellite image’s spectral reflectance, ...